Morfologie českého slovesa a tvoření deverbativ jako problém strojové analýzy češtiny - Osolsobě, Klára, 1964- (Spisy Masarykovy univerzity v Brně, Filozofická fakulta, 2011)
The text investigates the boundaries and possibilities of automation of Czech derivational morphology (e.g. several types of nouns and adjectives derived from verbs). The objective is to recapitulate the results of the formal description of Czech verb inflexion and regular derivation from verb form and to extend it to regular nominal derivation from verb stem and verb root (e.g. nouns and adjectives derived from verb). What the authors consider to be an essential benefit of their work is that they have designed and tested their formal description of word-formation through derivation linked to.